Effects of upgrading systems on energy conversion efficiency of a gasifier - fuel cell - gas turbine power plant. (15th October 2016) - Pedrazzi, Simone; Allesina, Giulio; Tartarini, Paolo
Highlights: An advanced gasifier-SOFC-MGT system is modeled. An overall electrical efficiency of 32.81% is reached. Influence of all the sub-system modeled on the power plant efficiency is discussed. Compression storage of syngas is taken into account. Abstract: This work focuses on a DG-SOFC-MGT (downdraft gasifier - solid oxide fuel cell - micro gas turbine) power plant for electrical energy production and investigates two possible performance-upgrading systems: polyphenylene oxide (PPO) membrane and zeolite filters. The first is used to produce oxygen-enriched air used in the reactor, while the latter separates the CO2 content from the syngas. In order to prevent power plant shutdowns during the gasifier reactor scheduled maintenance, the system is equipped with a gas storage tank. The generation unit consists of a SOFC-MGT system characterized by higher electrical efficiency when compared to conventional power production technology (IC engines, ORC and EFGT). Poplar wood chips with 10% of total moisture are used as feedstock. Four different combinations with and without PPO and zeolite filtrations are simulated and discussed. One-year energy and power simulation were used as basis for comparison between all the cases analyzed. The modeling of the gasification reactions gives results consistent with literature about oxygen-enriched processes. Results showed that the highest electrical efficiency obtained is 32.81%. This value is reached by the power plant equipped only with PPO membrane filtration. Contrary to the PPO filtering, zeolite filtration does not increase the SOFC-MGT unit performance while it affects the energy balance with high auxiliary electrical consumption. This solution can be considered valuable only for future work coupling a CO2 sequestration system to the power plant.